Identidade(s) do professor de matemática nas amarras escolares - Weber, Cássia Maiele (Universidade do Vale do Rio dos Sinos, 2015)
The paper aims to identify teacher identity(s) of Mathematics, constituted in discursive networks of contemporary school subjects. I analyze discourses produced by school staff (teaching coordinators, math teachers, teachers from other areas of knowledge and students from elementary and high school levels) of a private school, in the city of Novo Hamburgo, through questionnaires. Analytical tools used are: Identity and speech, in a post-metaphysical perspective, resulting respectively Bauman and Foucault. The discourse analysis and discursive recurrence observed in reports of the people of the research, pointed out that the math teacher has different identities depending on the discursive networks that produce them, but they converge on a responsible, ethical, interested in learning, empathic, dominating the content, committed fellowman, that instigates the construction of knowledge, creative, motivated, good example, consistent, polite, observer, proposing diverse, demanding, patient, organized activities, dedicated, love what you do, "explains well" the subject, takes questions from students, corrects the exercises, fair. From the characteristics presented in each discursive network, was created categories that identify the mathematics teacher as a multiple subject, inventive, powerful and miraculous, pointing to a teacher of mathematics that is a perfect and ideal professional.
Keywords: Identidade; Discurso; Professor; Matemática; Identity; Speech; Teacher; Mathematics